Affordances of models and modelling: a study of four technology design projects in the Swedish secondary school - Citrohn, Björn; Stolpe, Karin; Svensson, Maria; Bernhard, Jonte (Design and Technology Education: An International Journal, 2023)
This study aims to investigate affordances of models and modelling in design projects in technology education. To learn more about affordances when working with models and modelling, four Swedish technology teachers were interviewed using a narrative approach. Despite a small number of informants data were rich, containing detailed descriptions of sequences where students used models and modelling in ways not planned by the teachers. By using a qualitative, generic inductive approach, the narrative interviews revealed seven different affordances of models and modelling in the projects: Seeing different solutions; Finding possibilities and limitations in solutions; Representing an idea, structure or function; Communicating solutions with drawings; Making problems and solutions visible; Trial and error and learning from mistakes and finally Taking inspirations from each other’s solutions. Some conclusions and implications of the study are that when the students can see and use a wide variety of materials when modelling, they are more creative in finding solutions to design problems. The use of conceptual design in schools, leading to students performing trial and error using models to solve problems, might also be connected to the importance of a variety of materials. In the study, teachers describe how their students used models, trying different solutions, representing ideas, and trying, failing and trying again. All these modelling activities are important parts of a design process and might prove that the doing itself is a process of reflection.